Collaborative Marketing: A Study to Increase Indonesian Fish Consumption - Zefanya Alanza Chirstabel Loveldy; Imas Nurzanah; Impo Philipus Sitindaon; Ira Tutia; Tondi Sudaryo (Prosiding Industrial Research Workshop and National Seminar, 2018)
Even though Indonesia, as a maritime country, has high potency in fish production, its consumption is still very low. Different from Singapore and Malaysia which have high fish consumption level in 70 to 80 kg per capita per year. Fish consumption can be caused by several factors such as fish attributes (taste, appearance, odor, and price), consumer awareness, subjective norms, and consumption intention. The effect of these variables on consumption intention and consumption behavior is the primary focus of this paper. By using the method of distributing questionnaires to 400 respondents around Bandung Raya. The results show that there is an influence between two dimensions of the fish attributes, namely taste and odor, and also consumer awareness and subjective norms variable to consumption intention and behavior. Based on the findings, the results of this study explain the variables that affect the consumption intention and behavior, also its implication in Indonesia.